Performance and technology practices of virtual embodiment and interactivity - Broadhurst, Susan 1953-; Machon, Josephine 1979- (Palgrave, 2011)
"This book, now in paperback, interrogates the interaction between new technologies and performance practice, linking the sensuous contact that exists between the physical and virtual, along with the resultant corporeal transformation. It features writings from international contributors specializing in digital art and performance practices."